Insecticides and Their Mixtures for the Control of Plant Pests During the First Half of the Growing Season in Commercial Apple Orchards - Yanovskyi, Yu. P.; Sukhanov, S. V.; Fomenko, O. O.; Orlovskyi, M. Y. (Quarantine and plant protection, 2026)
Goal. To investigate the efficacy of insecticide Zedelis, MD (cyantraniliprole, 300 g/L) and its mixtures with Mospilan, WP (acetamiprid, 200 g/kg), Admiral, EC (pyriproxyfen, 100 g/L), and a plant oil-based adjuvant (Codacide 950, EC) in commercial apple orchards during the first half of the growing season against larvae of the San Jose scale (Quadraspidiotus perniciosus) and other phytophagous arthropods with coinciding phenology. The study also aimed to assess their effects on apple productivity parameters. Methods. Field experiments were conducted in 2024—2025 in commercial apple orchards under the conditions of the university’s training and production unit. The technical efficacy of Zedelis, MD and its mixtures with Mospilan, WP, Admiral, EC, and Codacide 950, EC at various application rates was evaluated against San Jose scale and other arthropods damaging leaves, shoots, and generative organs. Assessments were carried out according to standard methodologies in horticulture and plant protection. Results. Application of Zedelis, MD (0.2—0.3 L/ha) ensured a reduction in the population of San Jose scale larvae by 79.6—86.9%, aphids by (Disaphis devecta Walk., Aphis pomi Deg.) 79.0—92.1%, leafrollers by (Archips rosae L., Ptycholoma lecheana L., Pandtmis ribeana Hb.) 93.4—96.9%, and leaf-mining moths by (Lyonetia clerkella L., Cemisiostoma scitella L., Lithocolleris pyrifoliella Grsm., Lithocolleris corylifoliella H.) 90.4—96.7% within two weeks. Fruit damage caused by the codling moth (first generation) and currant leafroller did not exceed 0.3% compared to 6.9% in the control (water treatment), which was comparable to reference insecticides. An improvement in key biometric parameters was observed: the length of annual shoots and internodes increased by 23.1—30.7% and 8.3—12.5%, respectively; shoot thickness increased by 1.04—1.09 times; and leaf surface area increased by 37.3—47.8%. Mixtures of Zedelis, MD (0.2 L/ha) and Admiral, EC (0.75 L/ha) with Codacide 950, EC (1.0 L/ha) provided effective suppression of San Jose scale populations for up to three weeks, achieving 87.1—93.8% control. Mixtures of Zedelis, MD (0.25 L/ ha) Mospilan, WP (0.375 kg/ha), with Codacide 950, EC (1.0 L/ha) tu weeks, achieving control — 83,7—88,9%. Mixtures of Zedelis, MD (0.2 L/ha) with Admiral, EC (0.75 L/ha), as well as Zedelis, MD (0.25 L/ha) with Mospilan, WP (0.375 kg/ha), combined with Codacide 950, EC (1.0 L/ha), reduced aphid populations by 85.7—93.7% and 84.2—95.1%, leafrollers by 93.9—95.3% and 95.2—97.2%, leaf-mining moths by 93.4—96.4% and 93.1—94.2%, and pests of generative organs by 97.5% and 97.4%, respectively. The application of these mixtures significantly improved biometric indicators: annual shoot length increased by 38.5—46.1%, internode length by 12.5—16.6% and leaf surface area by 35.8—50.7%. No phytotoxic effects of Zedelis, MD or its mixtures were observed. Conclusions. The results of studies into the technical efficacy of the insecticide Cedelis, MD against major arthropods in apple orchards have led to its recommendation to the Ministry of Environmental Protection and Natural Resources of Ukraine for subsequent registration for use on apple trees at application rates of 0.2—0.3 l/ha and inclusion in the current national List of Pesticides and Agrochemicals authorized for use in Ukraine (Kyiv, 2026). Mixtures of the insecticide Cedelis, MD with the products Mospilan, VP, Admiral, KE and Codaside 950, EM should be recommended to growers as an effective control agent against first-generation San Jose scale and, at the same time, against other arthropods (taking into account the mode of action and economic threshold of harmfulness) in commercial apple orchards in the Forest-Steppe region of Ukraine during the first half of the growing season.